EL ROL DE LA USABILIDAD PERCIBIDA SOBRE LA CONFIANZA EN LAS SUBASTAS ONLINE - Eduardo Torres-Moraga; Cristobal Barra (RAE: Revista de Administração de Empresas, 2011)
Usability has been considered as a key variable that allows trust development in online environments. However, the relationship between these concepts has not been studied in depth to realize if the effect is direct or mediated. In this context, it is proposed that the perceived usability affects trust not in a direct way but considering the role of satisfaction as a mediator. This study considers the specific context of Internet auctions that represents a growing services market through Internet in Latin America. After testing the unidimensionality, reliability and validity of the measurement scales, hypotheses were tested using a structural equation modeling, a rival models strategy and a multi-sample analysis